Corona discharge-induced reduction of quinones in negative electrospray ionization mass spectrometry. Issue 69 (8th September 2017) - Pei, Jiying; Hsu, Cheng-Chih; Wang, Yinghui; Yu, Kefu
Abstract : Quinone reduction during negative ESI MS was illustrated to be closely related to corona discharge (CD). Abstract : Quinones, including 2, 6-dichloro-1, 4-benzoquinone (DCBQ), 1, 4-benzoquinone (BQ), methyl- p -benzoquinone (MBQ), 1, 4-naphthoquinone (1, 4-NQ), 1, 2-naphthoquinone (1, 2-NQ), and 1, 4-anthraquinone (AQ), generate M˙ − and [M + H] − anions, rather than deprotonated molecules, in negative electrospray ionization mass spectrometry (ESI MS), meaning a reduction occurs during the electrospray process. The ratio of the signal intensities of M˙ − and [M + H] − changed with the adjustment of experimental parameters. To gain more insight into the mechanism of quinone reduction, we explored the effect of experimental factors that are influential to corona discharge (CD). The results showed that a severe CD, such as high spray voltage, using water as spray solvent, no use of sheath gas, metal spray emitter, and slow flow rate of electrospray, facilitated the production of M˙ − ions while suppressing the production of [M + H] − ions. Therefore, a conclusion can be drawn that the reduction of quinones is closely related to CD. Moreover, the generation of M˙ − and [M + H] − is related to the quinone structure. Quinones with higher reduction potentials are more readily reduced to the [M + H] − form.